THE INTERPRETATION AND APPLIED STRATEGIES OF LOGO AND TAGLINE OF CIRCLE SHOES BRAND: A Study of Semiotics and Semantics - Sapa’at, Indra (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2018)
The paper entitled â€œThe Interpretation and Applied Strategies of Logo and Tagline of Circle Shoesâ€ discuses: (1) the interpretation of logo and tagline using semiotic approach, and (2) the strategies to create a logo and tagline using the approach of marketing on media. To analyse the data presented, the writer uses descriptive method. In descriptive method, observing, collecting, classifying and analysing data are conducted. This paper is meant to describe some factors how to create a good identity through logo and tagline besides the meanings of the logo and tagline themselves. Based on the analysis, the results of the research are: (1) the forms of logo give the idea of immortality, completeness, freedom, and protection, besides balance and destination. The black splotches color means a weakness of the product or company; perfection of a product certainly has weakness or deficiency. In addition, tagline shows the simplicity, elegance, uniqueness, timelessness, and memorableness, and (2) getting to know the product and the market target may be an effective strategy to make a logo and tagline that convey essential qualities, brand character, emphasize the benefit of the product, and align brand message with an intended market target.